KOMPETENSI KEPRIBADIAN GURU PAI DALAM MEMOTIVASI BELAJAR SISWA - Prasetya, Benny (EDUKASI: Jurnal Pendidikan Islam, 2013)
Personality of a teacher should be a role model for students. This is because the personality of the teacher have direct and cumulative effect on student behavior. Behavior of the teacher in teaching directly or indirectly have an influence on studentÃ¢â¬â¢s motivation either positive or negative in nature, means that, if the teachers personality displayed in accordance with the expectations of student teaching, students will be motivated to learn well.